2006
DOI: 10.1038/sj.tpj.6500355
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium and association with methamphetamine dependence/psychosis of μ-opioid receptor gene polymorphisms

Abstract: Several studies indicate that the m-opioid receptor plays a role in addiction not only to opiate drugs but also to alcohol and non-opiate addictive drugs. Our studies aim to reveal the associations between gene polymorphisms and methamphetamine (MAP) dependence/psychosis. We newly identified several polymorphisms and four substantial linkage disequilibrium (LD) blocks in the m-opioid receptor (OPRM1) gene. We found significant differences in both genotype and allele frequencies of the single-nucleotide polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…With regard to the Chr 10 QTL region, the genes that we have found to be DE in one or more of the 3 brain regions include, Oprm1, Esr1 (estrogen receptor 1), pcmt1 (protein-L-isoaspartate [D-aspartate] O-methyltransferase 1), ppil4 (peptidylprolyl isomerase [cyclophilin]-like 4), Hivep2 (human immunodeficiency virus type 1 enhancer binding protein 2) , Nhsl1 (NHS-like 1), Pex7 (peroxisome biogenesis factor 7), Map3k5 (mitogen activated protein kinase kinase kinase 5), Amd1 (S-adenosylmethionine decarboxylase 1), Cirbp (cold inducible RNA binding protein), Rfx4 (regulatory factor S, 4), Dmt2 (dorso-medial telencephalon gene 2) and Fgd6 (FYVE, RhoGEF and PH domain containing 6). Partly because good pharmacological tools exist to manipulate mu opioid receptors, but also because several polymorphisms and linkage disequilibrium blocks in human OPRM1 have been associated with MA dependence/psychosis (Ide et al, 2006) and because buprenorphine, a mu-opioid receptor partial agonist, attenuated the effects of MA on dopaminergic neuro-transmission in rats (Pereira et al, 2011), we have pursued a line of research that has demonstrated highly significant differences between MALDR and MAHDR mice in both opioid sensitivity (Eastwood and Phillips, 2013) and intake (Eastwood and Phillips, submitted). However, any of the genes in the QTL region could be relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the Chr 10 QTL region, the genes that we have found to be DE in one or more of the 3 brain regions include, Oprm1, Esr1 (estrogen receptor 1), pcmt1 (protein-L-isoaspartate [D-aspartate] O-methyltransferase 1), ppil4 (peptidylprolyl isomerase [cyclophilin]-like 4), Hivep2 (human immunodeficiency virus type 1 enhancer binding protein 2) , Nhsl1 (NHS-like 1), Pex7 (peroxisome biogenesis factor 7), Map3k5 (mitogen activated protein kinase kinase kinase 5), Amd1 (S-adenosylmethionine decarboxylase 1), Cirbp (cold inducible RNA binding protein), Rfx4 (regulatory factor S, 4), Dmt2 (dorso-medial telencephalon gene 2) and Fgd6 (FYVE, RhoGEF and PH domain containing 6). Partly because good pharmacological tools exist to manipulate mu opioid receptors, but also because several polymorphisms and linkage disequilibrium blocks in human OPRM1 have been associated with MA dependence/psychosis (Ide et al, 2006) and because buprenorphine, a mu-opioid receptor partial agonist, attenuated the effects of MA on dopaminergic neuro-transmission in rats (Pereira et al, 2011), we have pursued a line of research that has demonstrated highly significant differences between MALDR and MAHDR mice in both opioid sensitivity (Eastwood and Phillips, 2013) and intake (Eastwood and Phillips, submitted). However, any of the genes in the QTL region could be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic association studies have focused on specific genes; e.g., Oprm1 (Ide et al, 2006). Bousman et al (2009) reviewed the genetic association studies for MA use disorders and noted that 18 genes within 38 studies identified significant associations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous pharmacogenetic studies of SNP rs2075572 have shown varying results. A Japanese study found no association of the G allele of this SNP with postoperative analgesic requirements, but found an association with increased risk of methamphetamine dependence and psychosis [3,25] . A Chinese study found no association between rs2075572 and subjective heroin-induced responses [22] .…”
Section: Discussionmentioning
confidence: 99%
“…SNPs frequencies of Japanese OPRM1 in regions other than in the transcript region were provided in a previous report. 12) In our study, 5 SNPs (Ϫ1748G/A, Ϫ1565T/C, Ϫ1045A/G, Ϫ172G/T, Ϫ38C/A) were detected in the transcriptional regulatory region. Frequently, DNA binding affinity to the transcription factor is influenced by base substitution in transcription factor binding region or its neighborhood.…”
Section: Discussionmentioning
confidence: 98%